2020
DOI: 10.1002/jlb.3ma0320-406rr
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 alleviates DSS-induced ulcerative colitis via inhibiting NLRP3 inflammasome activation

Abstract: 1,25‐dihydroxyvitamin D3 (1,25(OH)2D3, VitD3) is the major active ingredient of vitamin D and has anti‐inflammatory activity; however, the mechanism for this remains poorly understood. In this study, we found that VitD3 was able to abolish NOD‐like receptor protein 3 (NLRP3) inflammasome activation and subsequently inhibit caspase‐1 activation and IL‐1β secretion via the vitamin D receptor (VDR). Furthermore, VitD3 specifically prevented NLRP3‐mediated apoptosis‐associated speck‐like protein with a caspase‐rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…A later study showed that NEK7 may also be involved in inflammatory bowel disease mediated by NLRP3 inflammasome activation, the mechanism of which has been described in the previous section (Chen X. et al, 2019). Similarly, several studies demonstrated that the development of neuroinflammation post-traumatic brain injury, ventilator-induced lung injury, diabetic periodontitis, DSS-induced ulcerative colitis, and endometritis in cattle display a significant correlation with NEK7-involved NLRP3 inflammasome activation Kelly et al, 2019;Liu et al, 2019;Liu H. et al, 2020;Zhou et al, 2019Zhou et al, , 2020Cao et al, 2020). In a previous study, NEK7 was predicted to be a target for miR-664 involved in the proinflammatory response to influenza A (H7N9) virus, but direct evidence was lacking (Chan et al, 2016).…”
Section: Diseases Related To the Nlrp3 Inflammasomementioning
confidence: 88%
See 1 more Smart Citation
“…A later study showed that NEK7 may also be involved in inflammatory bowel disease mediated by NLRP3 inflammasome activation, the mechanism of which has been described in the previous section (Chen X. et al, 2019). Similarly, several studies demonstrated that the development of neuroinflammation post-traumatic brain injury, ventilator-induced lung injury, diabetic periodontitis, DSS-induced ulcerative colitis, and endometritis in cattle display a significant correlation with NEK7-involved NLRP3 inflammasome activation Kelly et al, 2019;Liu et al, 2019;Liu H. et al, 2020;Zhou et al, 2019Zhou et al, , 2020Cao et al, 2020). In a previous study, NEK7 was predicted to be a target for miR-664 involved in the proinflammatory response to influenza A (H7N9) virus, but direct evidence was lacking (Chan et al, 2016).…”
Section: Diseases Related To the Nlrp3 Inflammasomementioning
confidence: 88%
“…The three natural products oridonin (He et al, 2018;Liu H. et al, 2020), artemisinin (Kim et al, 2019), and ginsenoside Rg3 (Shi et al, 2020) have been reported to have similar functions in abrogating NEK7-NLRP3 interaction, as corroborated by different mouse models (He et al, 2018;Kim et al, 2019;Shi et al, 2020). Seven chemical medicines, including glucosamine (Chiu et al, 2019), metformin (Zhou et al, 2019, glibenclamide (Liu H. et al, 2020), ALK inhibitors (ceritinib and lorlatinib) (Zhang et al, 2018), autophagy inhibitors (chloroquine and bafilomycin A1) (Torp et al, 2019), and 1,25(OH)2D3 (Cao et al, 2020), have also shown significant inhibitory effects on various aspects of the NEK7-NLRP3 interaction. To better understand the therapeutic effect of molecular inhibitors and medicines, more tightly controlled samples from different species urgently need to be included in future studies.…”
Section: Inhibitors and Their Application To Diseasesmentioning
confidence: 95%
“…In obese patients, VDR polymorphisms were associated with increased inflammasome component expression, proinflammatory cytokine secretion and gut permeability, or dysbiosis, raising circulating LPS (173). Additionally, VitD3activated VDR and SR9009-activated Rev-erbs also protect from DSS-induced colitis (126,142), which then emphasizes the use of such NR-targeted approaches to control inflammatory bowel diseases ( Table 1). It is noteworthy that numerous compounds derived from Chinese medicine are able to control the inflammasome pathway.…”
Section: Intestinal Diseasesmentioning
confidence: 99%
“…Furthermore, activated VDR inhibited NLRB3 binding to NEK7, and blocked NLRP3mediated ASC oligomerization as well as ROS accumulation, altogether, this disabled the activation of NLRP3 inflammasome. Furthermore, 1,25-D 3− promoted polyubiquitination of NLRP3 resulted in the degradation and elimination of the protein through autophagy (106).…”
Section: Vitamin D Receptor (Vdr)mentioning
confidence: 99%